The maturity status but not the relative age influences elite young football players` physical performance - Peña-González, I.; Javaloyes, A.; Cervelló, E.; Moya-Ramón, M. (Science and Medicine in Football, 2022)
Talent identification and selection process in young football is based on coaches` decisions regarding the players` performance at early ages. The aim of this study was to show how the maturity status and the relative age impact on young football players` physical performance and their coaches` efficacy expectations. The physical performance (1RM, Peak power output [PPO], 30-m sprint and t-test) of 118 young football players (U13 to U15; and their coaches` efficacy expectations were assessed. Relative age was calculated according to the players` date of birth within their selection year. The maturity status was estimated as the years from/to their peak height velocity (PHV). Linear regression analyses showed a significant relationship between players` physical performance and their maturity status but not with their relative age. In contrast, the maturity status of players only was associated to the coaches` efficacy expectations in the 1RM and PPO tests, whereas the relative age was a predictor of the coaches` expectations about players` performance in the t-test. These findings may be important for coaches and managers in young football academies since inter-individual differences in the maturity status but not in the relative age are related to physical performance despite the coaches` expectations.